ARABIC TEACHER'S EXPERIENCE IN OVERCOMING ONLINE-BASED LEARNING PROBLEMS AT ISLAMIC SENIOR HIGH SCHOOL 1 JAMBI CITY - Mu’minatul Latifah; Mohamad Muspawi; Friscilla Wulan Tersta (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: This thesis discusses the Experience of Arabic Teachers in Overcoming Online-Based Learning Problems at Islamic Senor High School 1 Jambi City. Teacher experience is an event that has happened to a teacher so that from that experience can be taken lessons and conclusions and for teachers can be a reference in teaching. From the existence of experience, there will be a good learning process. This research aims to find out how the experience of Teachers of Arabic Islamic Senor High School 1 Jambi City in overcoming problems in carrying out the teaching and learning process at Islamic Senor High School1 Jambi City and know the efforts made by Arabic teachers. This research is descriptive qualitative research using observation, interviews and documentation in data collection techniques. While the data analysis techniques used are data reduction, presentation of conclusion drawing data. The data validity technique used is triangulation.